2016
DOI: 10.1111/ssm.12162
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Teachers: Concerns About Implementing a Science Program

Abstract: The purpose of this study was to examine elementary teachers' science teaching concerns after participating in a two-year extensive and sustained science professional development intervention. The intervention consisted of two types of teacher professional development across two years including: (a) summer institutes (60 hours across two years) which provided training on curriculum units, inquiry-based instructional strategies, problem-based learning, classroom management, and technology use in the classroom; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(38 reference statements)
0
10
0
1
Order By: Relevance
“…Professional development should model exemplary instruction differentiated to meet the needs of all learners and utilize classroom-specific curricula (Duschl et al, 2007). In a recent study by Dailey and Robinson (2016), teachers indicated they preferred to take the role of the student as the professional development instructor guided them through their classroom-specific unit lessons. Teachers appreciated the opportunity to view the perspective of the student by completing the activities designed for their classroom.…”
Section: Professional Development To Support Teachers In Engineeringmentioning
confidence: 99%
See 4 more Smart Citations
“…Professional development should model exemplary instruction differentiated to meet the needs of all learners and utilize classroom-specific curricula (Duschl et al, 2007). In a recent study by Dailey and Robinson (2016), teachers indicated they preferred to take the role of the student as the professional development instructor guided them through their classroom-specific unit lessons. Teachers appreciated the opportunity to view the perspective of the student by completing the activities designed for their classroom.…”
Section: Professional Development To Support Teachers In Engineeringmentioning
confidence: 99%
“…Increasing opportunities for students to engage in engineering design practices is promising, but there are several obstacles that need to be addressed. For example, elementary teachers often do not have the time, knowledge, skills, or confidence to provide students investigative opportunities in science (Banilower, Smith, Pasley, & Weiss, 2006; Dailey & Robinson, 2016; Fulp, 2002; Murphy, Neil, & Beggs, 2007). Furthermore, teachers face various struggles with the addition of engineering design practices (Brophy, Klein, Portsmore, & Rogers, 2008) as a requirement of NGSS (Achieve, Inc., 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations